ASSESSMENT OF MATERNAL SATISFACTION WITH EPIDURAL AND NON-EPIDURAL ANALGESIA SERVICE AT THE DEPARTMENT OF OBSTETRICS AND GYNECOLOGY AT BACH MAI HOSPITAL IN 2025. (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the satisfaction of parturients using the labor analgesia service with epidural anesthesia and to identify factors associated with their satisfaction. Method: A cross-sectional study was conducted on 111 women who experienced vaginal deliveries at the Department of Obstetrics and Gynecology at Bach Mai Hospital, Hanoi, from July to September 2025. Result: The majority had a high level of education and expressed concern about labor pain. Over 90% of women were satisfied with the analgesia service package in terms of facility quality, staff attitude, and administrative procedures. The continued care, encouragement, and positive support provided by midwives significantly influenced women’s satisfaction (p < 0.01).Conclusion: Most mothers were satisfied with the quality of the labor analgesia service. Midwives’ attention, care, and emotional support play an essential role in enhancing the childbirth experience and women’s satisfaction. Strengthening midwives’ communication and counseling skills is crucial for improving patient care.
Keywords: patient satisfaction; epidural anesthesia; midwife; vaginal delivery.